Doha in the Dumps: The Bilateral Option. Whither Canadian Trade Policy - Dymond, William (Eurostudia, 2007)
AbstractThis article takes Canadian trade politics in order to demonstrate that the mixture of multi- and bilateral negotiations is a solution just for yesterday’s problems. First the article provides an account of the present situation of the Doha Development Round. Second it discusses Canada’s interest in bilateral agreements before it analyzes the present conditions for international trade. The final section is dedicated to the political options resulting from that situation.